2022
DOI: 10.3389/fpsyg.2022.1030405
|View full text |Cite
|
Sign up to set email alerts
|

The key enablers of competitive advantage formation in small and medium enterprises: The case of the Ha’il region

Abstract: The primary objective of this research is to establish the extent to which small and medium-sized businesses (SMEs) in the Ha’il region benefit from a significant competitive advantage brought about by an entrepreneurial mindset (innovativeness, proactiveness, risk-taking, competitive aggressiveness, and autonomy). To achieve these objectives, the study used a questionnaire to collect data. A total of 220 SMEs in the Ha’il region were surveyed. The participants completed an online self-administered survey and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 86 publications
(127 reference statements)
3
0
0
Order By: Relevance
“…Participant 4 emphasized, " Mandatory training in modern teaching and assessment techniques is crucial for both new and existing faculty members , " while Participant 26 noted, " Comprehensive professional development for all of KKU’s human resources , including faculty and staff , is essential for achieving the university’s strategic goals ." These findings align with Thomran et al [ 28 ], which argues that professional development is fundamental to increasing competitiveness, and with Hashim’s [ 3 ] research, underlining the importance of continuous professional growth for academic staff.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Participant 4 emphasized, " Mandatory training in modern teaching and assessment techniques is crucial for both new and existing faculty members , " while Participant 26 noted, " Comprehensive professional development for all of KKU’s human resources , including faculty and staff , is essential for achieving the university’s strategic goals ." These findings align with Thomran et al [ 28 ], which argues that professional development is fundamental to increasing competitiveness, and with Hashim’s [ 3 ] research, underlining the importance of continuous professional growth for academic staff.…”
Section: Discussionsupporting
confidence: 89%
“…Participant 14 observed, " The university’s study plans undergo regular evaluations , with curricula designed to sequence and integrate , equipping graduates with the skills and qualifications the job market seeks . " This aligns with Thomran et al [ 28 ], whose research suggests that a key competitive advantage is graduates possessing knowledge, skills, and values in sync with market needs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Creativity and innovation are crucial for success in today's world, where new ideas and solutions are needed to solve complex problems. The results of the study revealed that the students generally perceive themselves as being involved in creative thinking activities and participating in creativity and innovation training at the university which support the proposed idea of the authors, in addition to that the results is in line with results of Ghosh, 2015;Huang et al, 2022;Ye et al, 2022;Thomran et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…In the hope to elucidate a clearer relationship between entrepreneurial orientation and firm performance, the researchers turned their attention to competitive aggressiveness, a manifestation of competitiveness (Aldabbas & Oberholzer, 2023;Blok, 2018;Shajrawi & Aburub, 2022;Thomran, Alshallaqi, Al-Mamary, & Abdulrab, 2022). Argued to be the key dimension of entrepreneurial orientation affecting firm performance, competitive aggressiveness is defined as "the type of intensity and head-tohead posturing that new entrants often need to compete with existing rivals."…”
Section: Competitive Aggressivenessmentioning
confidence: 99%